2021
DOI: 10.1073/pnas.2007815118
|View full text |Cite
|
Sign up to set email alerts
|

Encoding memory in tube diameter hierarchy of living flow network

Abstract: The concept of memory is traditionally associated with organisms possessing a nervous system. However, even very simple organisms store information about past experiences to thrive in a complex environment—successfully exploiting nutrient sources, avoiding danger, and warding off predators. How can simple organisms encode information about their environment? We here follow how the giant unicellular slime mold Physarum polycephalum responds to a nutrient source. We find that the network-like body plan of the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 52 publications
1
55
1
1
Order By: Relevance
“… Armus et al (2006) have identified in Paramecium caudatum that this protist is able to develop a preference for illumination level using a mild electric shock as a reinforce. Fungus-like organisms such as Physarum polycephalum has been shown to exhibit a primitive type of learning ( Boisseau et al, 2016 ; Boussard et al, 2019 ; Kramar and Alim, 2021 ). Moreover, this unicellular multinucleate plasmodium was observed to acquire new thermotactic behaviors when exposed to a temperature gradient and a source of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“… Armus et al (2006) have identified in Paramecium caudatum that this protist is able to develop a preference for illumination level using a mild electric shock as a reinforce. Fungus-like organisms such as Physarum polycephalum has been shown to exhibit a primitive type of learning ( Boisseau et al, 2016 ; Boussard et al, 2019 ; Kramar and Alim, 2021 ). Moreover, this unicellular multinucleate plasmodium was observed to acquire new thermotactic behaviors when exposed to a temperature gradient and a source of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the Physarum could be remembering being a single entity and be motivated to return to that state as a kind of homeostasis. Physarum is known to be capable of remembering past experiences [21][22][23][24], and it is possible that the rapid merging is a kind of regenerative/repair response (anatomical homeostasis) that acts faster than individual pieces can acquire an independent identity.…”
Section: Discussionmentioning
confidence: 99%
“…Body design can be leveraged to alleviate on even replace control demands, as in passive (brain-and control-less) walking robots (McGeer, 1990). For a recent experimental and computational demonstration of how a slime mould's hierarchical network morphology may be seen as modelling its nutrient environment at fast timescales see Kramar and Alim (2021). See Sect.…”
Section: The Free Energy Principle (Fep): a Short Summarymentioning
confidence: 99%